2019
DOI: 10.1128/aac.02122-18
|View full text |Cite
|
Sign up to set email alerts
|

DS86760016, a Leucyl-tRNA Synthetase Inhibitor with Activity against Pseudomonas aeruginosa

Abstract: DS86760016 is a new leucyl-tRNA-synthetase inhibitor at the preclinical development stage. DS86760016 showed potent activity against extendedspectrum multidrug-resistant Pseudomonas aeruginosa isolated from clinical samples and in vitro biofilms. In a murine catheter-associated urinary tract infection model, DS86760016 treatment resulted in significant eradication of P. aeruginosa from the kidney, bladder, and catheter without developing drug resistance. Our data suggest that DS86760016 has the potential to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…To further determine the effect of azithromycin against planktonic cells and biofilm formation on a solid surface, we performed a time-kill kinetic study using a catheter piece as a solid surface objective, as described earlier (Kumar et al, 2019), although azithromycin showed a substantial 1.86 log 10 reduction in planktonic cell counts at 6 h as compared to the drug-free control and but no effect at 24 h post-incubation (Figure 2A and Supplementary Figure 3). Possibly, overexpression of multidrug efflux pumps could be the reason of its poor activity against P. aeruginosa in LB media, as potent-activity of azithromycin has been observed in the presence of known efflux pump inhibitors or eukaryotic media (RPMI 1640) (Buyck et al, 2012).…”
Section: In Vitro Biofilm Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…To further determine the effect of azithromycin against planktonic cells and biofilm formation on a solid surface, we performed a time-kill kinetic study using a catheter piece as a solid surface objective, as described earlier (Kumar et al, 2019), although azithromycin showed a substantial 1.86 log 10 reduction in planktonic cell counts at 6 h as compared to the drug-free control and but no effect at 24 h post-incubation (Figure 2A and Supplementary Figure 3). Possibly, overexpression of multidrug efflux pumps could be the reason of its poor activity against P. aeruginosa in LB media, as potent-activity of azithromycin has been observed in the presence of known efflux pump inhibitors or eukaryotic media (RPMI 1640) (Buyck et al, 2012).…”
Section: In Vitro Biofilm Activitymentioning
confidence: 99%
“…The effect of azithromycin and clindamycin on P. aeruginosa biofilm formation was assessed as described previously (Sharma et al, 2009;Barman et al, 2016;Kumar et al, 2019). Briefly, the overnight-grown culture of P. aeruginosa PAO1 in TSB was pelleted and resuspended in Luria-Bertani broth containing 0.2% glucose (10 7 CFU/ml).…”
Section: In Vitro Biofilm Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment options for nosocomial Gram-negative infections are very limited. The poor activities of these antibiotics on bacterial biofilms and the increasing prevalence of MDR P. aeruginosa leave the physicians with very limited choices to effectively treat these patients ( Bassetti et al, 2018 ; Ciofu and Tolker Nielsen, 2019 ; Kumar et al, 2019 ). Antibiotic-resistant biofilms exist widely in P. aeruginosa infection, which is one of the important reasons for the failure of antibacterial treatment.…”
Section: Discussionmentioning
confidence: 99%